Analisis Tentang Hubungan Antara Cerpen Reaching For The Sky Karya Mitchell Waldman dengan Teori Strukturalisme Genetik - Nurmartanti, Oryza (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The journal entitled "Analysis of the Relationship between Reaching For The Sky Short Story and Genetic Structural Theory" aims to describe the genetic structuralistic relationship shown in the study of Reaching For The Sky short stories. This research uses descriptive analysis method by using literary sociology analysis techniques. Short Story Reaching For The Sky is an interesting to be chosen because it is thought to show the relationship between structuralism theory and social inequality.The results showed that the short story Reaching For The Sky by Mitchell Waldman is work that is full of criticism about social class inequality that occurs in Brooklyn, New York, USA. This short story besides carrying the theme of social class, can also be examined more deeply using the theory of Genetic Structuralism. This can be achieved because between the short story and the author, there is a very close relationship. Can be identified through the author's background and what is in the short story. Characters, settings, story lines, enough to represent the correlation of short stories, authors and theories that support the link between the short storyline and genetic structuralism. Among these are: facts of humanity, collective subjects, worldview, structuration and dialectics of understanding.